2017
DOI: 10.1136/ejhpharm-2016-001146
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of antibiotic prescribing for adult inpatients at Sultan Qaboos University Hospital, Sultanate of Oman

Abstract: ObjectiveLittle is known into the prudent use of antibiotics in hospitals in Oman. This study is to evaluate antibiotic prescribing by measuring the overall compliance with the local antibiotic prescribing guidelines.MethodsAn observational study involving 366 patients’ admission episodes as determined by power analysis on patients (≥18 years) on oral and/or parenteral antibiotic during admission, in the period of 10 weeks (1 February–15 April, 2014). The adapted audit tool of the Barking, Havering and Redbrid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 11 publications
0
17
0
Order By: Relevance
“…The three most common antimicrobials requiring modifications in our study were meropenem, piperacillin/tazobactam and vancomycin. This largely reflects the prescribing pattern of antibiotics as SQUH as shown by Al Maliky et al (Al-Maliky et al, 2018) where the highest number of prescriptions were made for piperacillin/tazobactam (22%), followed by azithromycin (15%) and then meropenem (11% of total antimicrobial prescriptions). Interventions on meropenem were mainly in the ICU (>90%).…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…The three most common antimicrobials requiring modifications in our study were meropenem, piperacillin/tazobactam and vancomycin. This largely reflects the prescribing pattern of antibiotics as SQUH as shown by Al Maliky et al (Al-Maliky et al, 2018) where the highest number of prescriptions were made for piperacillin/tazobactam (22%), followed by azithromycin (15%) and then meropenem (11% of total antimicrobial prescriptions). Interventions on meropenem were mainly in the ICU (>90%).…”
Section: Discussionmentioning
confidence: 63%
“…There are several proposed explanations for this high rate. Firstly, it is known that the ICU represents the heaviest antibiotic burden within the hospital (Brusselaers et al, 2011) and studies have shown that up to 60% of antibiotics prescribed in ICUs are inappropriate, which is higher than other disciplines of care (Luyt et al, 2014;Al-Maliky et al, 2018). Additionally, AMS services are provided on a small scale in the ICU with weekly meetings between an ICU team doctor, and infectious diseases (ID) consultant and a CP.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies from Bahrain reported increased use of broad spectrum antibiotics like ceftriaxone due to resistance to first and second line options [31,32]. One Omani study reported that 90% of antibiotic prescriptions were for broad spectrum antibiotics due to lack of adherence with antimicrobial guidelines and policies [40]. An oral presentation in 2013 also reports a decline in using broad-spectrum antibiotics in an UAE hospital as a result of antimicrobial stewardship interventions in that setting [59].…”
Section: Outcomes Of Hospital Adoption Of Asps In Gcc Countriesmentioning
confidence: 99%
“…Articles excluded were 57 reviews, 78 articles without prescribing patterns, 53 that came from outside the Gulf region, and 128 articles with outcomes other than inappropriateness; the remaining 18 articles were included. [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] In the second step, a total of 2453 articles were searched, and after removing duplications 2357 were from PubMed, two from Embase and one from Elsevier. Nine hundred and one articles were excluded based on the abstract, and 1349 based on the title; 110 articles were included and studied thoroughly.…”
Section: Results and Findings General Characteristicsmentioning
confidence: 99%